2006
DOI: 10.1021/jp0607824
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Multiphoton Dissociation Spectroscopic Analysis of Peptides and Oligosaccharides by Using Fourier Transform Ion Cyclotron Resonance Mass Spectrometry with a Midinfrared Free-Electron Laser

Abstract: The fragmentation of peptides and oligosaccharides in the gas phase was investigated by means of electrospray ionization Fourier transform ion cyclotron resonance (FTICR) mass spectrometry coupled with dissociation by a laser-cleavage infrared multiphoton dissociation (IRMPD) technique. In this technique, an IR free-electron laser is used as a tunable source of IR radiation to cause cleavage of the ionized samples introduced into the FTICR cell. The gas-phase IRMPD spectra of protonated peptides (substance P a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…In the MICRA system the FEL irradiation is perpendicular to the magnetic field, while for the Bruker system it is parallel to the field. A third FTICR‐FEL facility utilizes a free electron laser at the Science University of Tokyo (SUT) to irradiate ions in a commercial (Bruker) 4.7 T FTICR mass spectrometer (Fukui et al, 2006).…”
Section: Recent Irmpd Experiments Using Free Electron Lasers and Optimentioning
confidence: 99%
See 1 more Smart Citation
“…In the MICRA system the FEL irradiation is perpendicular to the magnetic field, while for the Bruker system it is parallel to the field. A third FTICR‐FEL facility utilizes a free electron laser at the Science University of Tokyo (SUT) to irradiate ions in a commercial (Bruker) 4.7 T FTICR mass spectrometer (Fukui et al, 2006).…”
Section: Recent Irmpd Experiments Using Free Electron Lasers and Optimentioning
confidence: 99%
“…The Ohanessian group used the CLIO FEL and a Paul trap to obtain the IRMPD spectra of a 12‐residue fragment of stathmin in its phosphorylated and non‐phosphorylated forms, in conjunction with structural characterization of protonated phosphorylated serine, threonine, and tyrosine (Correia et al, 2008). Fukui and co‐workers at the Tokyo University of Science used the FEL‐SUT to study protonated substance P and protonated angiotensin II over the 5.7–9.5 µm wavelength range and observed mainly y/b‐type fragment ions (Fukui et al, 2006). Spectra of the largest system for which IRMPD spectra have been obtained to date, the 104 amino acid cytochrome c , showed clearly resolvable bands in the amide I and II spectral regions (Fig.…”
Section: Recent Irmpd Experiments Using Free Electron Lasers and Optimentioning
confidence: 99%
“…Upon exiting the guide, the ions encounter the ICR cell at ground potential and slow down to a low kinetic energy (3 eV in this example), so that they can be efficiently captured in the cell. Figure adapted from Polfer et al [154] A.M. Rijs and J. Oomens [158]. Furthermore, the new IR FEL at the Fritz Haber Institute in Berlin has very recently been applied to obtain IR ion spectra [159].…”
Section: Irmpd Spectroscopymentioning
confidence: 99%
“…Several studies have explored the use of IRMPD in an FTICR mass spectrometer for the analysis of oligosaccharides [16,[31][32][33][34][35]. For example, Lancaster et al compared the IRMPD spectra of O-linked and N-linked type oligosaccharides and found that cross-ring cleavages were observed only for the N-type oligosaccharides that are not readily fragmented by using CAD [16].…”
mentioning
confidence: 99%
“…While the spectra were informative, poor signal-to-noise ratios often made spectral interpretation difficult [31]. Fukui et al used wavelength-tunable IRMPD in an FTICR mass spectrometer to determine the optimal dissociation wavelengths for sodium-cationized oligosaccharides [32]. While this technique is powerful, these types of lasers are not readily available.…”
mentioning
confidence: 99%